2001
DOI: 10.1111/j.1151-2916.2001.tb00760.x
|View full text |Cite
|
Sign up to set email alerts
|

R‐Curve Behavior of In Situ Toughened α‐SiAlON Ceramics

Abstract: R-curves of single-phase Y-and Ca-containing ␣-SiAlON ceramics have been measured. They range from flat ones for fine-grain ceramics to pronounced rising ones when large elongated grains are present. The highest toughness measured reached 11.5 MPa⅐m 1/2 over a crack extension of about 1000 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
(10 reference statements)
1
19
1
Order By: Relevance
“…It can be pointed out here that R-curves are exhibited by a wide range of SiAlON materials, e.g. Y-␣-SiAlON, 2 in situ toughened Y-␣-SiAlON, Ca-␣-SiAlON, 39 etc. Depending on the amount of seed crystals, a peak toughness of 10 MPa m 1/2 or little higher was recorded in these ceramics.…”
Section: R-curve Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…It can be pointed out here that R-curves are exhibited by a wide range of SiAlON materials, e.g. Y-␣-SiAlON, 2 in situ toughened Y-␣-SiAlON, Ca-␣-SiAlON, 39 etc. Depending on the amount of seed crystals, a peak toughness of 10 MPa m 1/2 or little higher was recorded in these ceramics.…”
Section: R-curve Behaviormentioning
confidence: 97%
“…see Refs. 35,[37][38][39]. Table 3 presents the summary of the mechanical property data of some selected SiAlON ceramics and such data illustrate a large variation in apparent hardness and toughness properties.…”
Section: R-curve Behaviormentioning
confidence: 98%
“…According to Chen and Rosenflanz [1], in order to make elongated α-Sialon grains, it is important to control the nucleation rate and form only a small number of α-Sialon nuclei that grow into elongated grains without hindrance from impingement with other α-Sialon grains. Zenotchkine et al introduced less than 5 % of α-Sialon seeds in the starting powder mixture and obtained elongated α-Sialon grains growing from the seeds [2]. Nordberg et al reported that growth of elongated α-Sialon grains was promoted by the presence of a liquid rich in Al and O [3].…”
Section: Introductionmentioning
confidence: 98%
“…However, α-Sialon exhibits lower fracture toughness and flexural strength than β-Sialon or β-Si 3 N 4 consisting of elongated grains due to the microstructure consisting of equiaxial grains. Since Chen and Rosenflanz reported that the properties of α-Sialon were improved by establishing a microstructure consisting of elongated grains, there have been many reports on α-Sialon ceramics with elongated grains [1][2][3][4][5]. According to Chen and Rosenflanz [1], in order to make elongated α-Sialon grains, it is important to control the nucleation rate and form only a small number of α-Sialon nuclei that grow into elongated grains without hindrance from impingement with other α-Sialon grains.…”
Section: Introductionmentioning
confidence: 99%
“…The test bar was next subject to 4-point bending with a gradual increase of load, in small increments, to allow in situ monitoring of crack extension following the method described in Ref. 25.…”
Section: Measurement Of Mechanical Propertiesmentioning
confidence: 99%